2021
DOI: 10.1097/cu9.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine levels as markers of paralytic ileus following robotic radical prostatectomy at different pneumoperitoneum pressures

Abstract: Background: To evaluate intraoperative and postoperative cytokines in patients who underwent robotic prostatectomy (RP) at a pressure of 12 or 15 mm Hg, and the risk of postoperative ileus. Materials and methods: We presented the first series evaluating intraoperative and postoperative cytokines in patients undergoing RP at a pressure of 12 or 15 mm Hg by a single surgeon. Changes in cytokine concentrations were shown to correlate with surgical outcomes and pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…We also found that lower pressures were associated with reduced rates of ileus, and furthermore, this was associated with alterations in postoperative cytokine levels favouring an anti-inflammatory response. 22 The latter has not been explicitly confirmed in the current study, with the medians for IL-1β, IL-2, IL-17A, TNFα and IFNγ showing no statistically significant differences between pressures or study groups.…”
Section: Discussioncontrasting
confidence: 64%
“…We also found that lower pressures were associated with reduced rates of ileus, and furthermore, this was associated with alterations in postoperative cytokine levels favouring an anti-inflammatory response. 22 The latter has not been explicitly confirmed in the current study, with the medians for IL-1β, IL-2, IL-17A, TNFα and IFNγ showing no statistically significant differences between pressures or study groups.…”
Section: Discussioncontrasting
confidence: 64%
“…8 Hampson et al studied cytokine levels in 10 RP patients at 15 mmHg vs 12 mmHg and found lower levels of cytokines associated with a risk of ileus but without any clinical differences in outcomes. 13 We previously performed a retrospective study of 300 patients in each group after switching from a routine of 15 mmHg to 6 mmHg and found a modest improvement in pain with no increase in complications or other negative impact. 14 We therefore designed the current randomized study to carefully measure pain scores and analgesic use as well as physiological measures and other clinically meaningful perioperative RP outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…8 Hampson et al studied cytokine levels in 10 RP patients at 15 mmHg vs 12 mmHg and found lower levels of cytokines associated with a risk of ileus but without any clinical differences in outcomes. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence from currently published studies that can inform clinical practice includes a retrospective study in 2018 [16] and two randomized controlled trials (RCTs) published in 2020 [17] and 2021 [18]. Tese studies suggest that low IAP during RARP is associated with a signifcant reduction in the incidence of postoperative bowel obstruction compared with standard IAP [16][17][18]. However, the impact of low IAP on operative time, length of hospital stay, and other surgical outcomes is unknown.…”
Section: Introductionmentioning
confidence: 99%